The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.30564/jaeser.v4i2.2812
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on Solar Reflectance of White Cool Roof Coatings: Natural Weathering and the Influence on Building Energy Needs for Different Climate Conditions in Brazil

Abstract: The use of cool materials on the building envelope is one of the most cost-effective ways to increase indoor thermal comfort conditions in hot climates and decrease the cooling energy needs. Despite the benefit of reducing cooling loads, researches have demonstrated that aging of roof coatings changes the initial SR, which influences the long term building thermal and energy performance. Thus, this work presents preliminary natural weathering tests performed on samples of nine white coatings exposed to natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In Brazil, several studies have been reported by [9,15,16,[25][26][27][28][29], with ongoing research being carried out by the members of the University of São Paulo and Federal University of Santa Catarina. In the studies proposed by [15], a white cool paint was exposed in 4 cities of the country (São Paulo, Pirassununga, Belém and São Sebastião) and presented different levels of degradation between the sites, caused by different weather conditions, microflora, and pollutants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Brazil, several studies have been reported by [9,15,16,[25][26][27][28][29], with ongoing research being carried out by the members of the University of São Paulo and Federal University of Santa Catarina. In the studies proposed by [15], a white cool paint was exposed in 4 cities of the country (São Paulo, Pirassununga, Belém and São Sebastião) and presented different levels of degradation between the sites, caused by different weather conditions, microflora, and pollutants.…”
Section: Literature Reviewmentioning
confidence: 99%